2009
DOI: 10.1007/s11031-009-9152-2
|View full text |Cite
|
Sign up to set email alerts
|

Antecedents of everyday positive emotions: An experience sampling analysis

Abstract: The focus of this study is on everyday positive emotions and their relations to critical appraisal antecedents. Following from classical appraisal theory and Pekrun's (2006) control-value theory of achievement emotions, two research questions were addressed, namely whether cognitive appraisals of control and value were related to discrete positive emotions in everyday situations and whether control and value antecedents interact in predicting these emotions. We further investigated whether control/ value and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

18
180
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 208 publications
(202 citation statements)
references
References 62 publications
18
180
0
4
Order By: Relevance
“…More explicitly, the control-value theory postulates a noncompensatory relation of value and control in predicting boredom, so that the lowest degree of boredom implies increased value and control. In this regard, Goetz et al (2010) found that control and value appraisals predict positive emotions in a multiplicative manner. They identified an interaction effect and assumed that perceived control and positive emotional experiences were greater in situations of high subjective value while controlling for the main effects.…”
Section: Control-value Antecedents Of Achievement Emotionsmentioning
confidence: 95%
See 2 more Smart Citations
“…More explicitly, the control-value theory postulates a noncompensatory relation of value and control in predicting boredom, so that the lowest degree of boredom implies increased value and control. In this regard, Goetz et al (2010) found that control and value appraisals predict positive emotions in a multiplicative manner. They identified an interaction effect and assumed that perceived control and positive emotional experiences were greater in situations of high subjective value while controlling for the main effects.…”
Section: Control-value Antecedents Of Achievement Emotionsmentioning
confidence: 95%
“…The scarce existing results indicate significant interactions between control and value appraisals predicting everyday positive emotions (cf. Goetz et al 2010) as well as different effects of control appraisals on academic boredom in cases of low versus high value (Bieg et al 2013).…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…A related emotion, pride, has also been assessed in attribution research (Tracy & Robins, 2007;Nickel & Spink, 2010). Both pride and self-esteem should respond similarly to attributions, and controllability in particular has been hypothesised have an important effect on these feeling states (Goetz, Frenzel, Stoeger, & Hall, 2010). Further, the perceived mutability hypothesis (Roese & Olson, 2007) points to an important role for the interaction of controllability and generalisability dimensions by describing how poor performance is less damaging to selfesteem when the circumstance is open to modification (e.g.…”
Section: Affective Consequencesmentioning
confidence: 99%
“…For example, experience sampling methods could better inform our understanding of how teachers compare themselves to others in real-life classroom settings (cf. Goetz, Frenzel, Stoeger, & Hall, 2010), with objective health indicators also serving as more ecologically valid outcome measures (e.g., teacher self-efficacy and cortisol; Schwerdtfeger, Konermann, & Schonhofen, 2008).…”
Section: Limitations and Future Directionsmentioning
confidence: 99%